Deconstructing Multiteam System Action: Development and Content Validation of a Multilevel Multiteam System Action Taxonomy. Issue 3 (27th May 2021) - Torres, Elisa M.; Wallace, David M; Zaccaro, Stephen J; Dubrow, Samantha
ABSTRACT: Current theories of goal-directed action in networks of closely collaborating teams, have yet to provide a framework that can assist in identifying specific points of multiteam system (MTS) action that led to performance breakdowns. Expanding upon previous frameworks, we develop an MTS action taxonomy detailing 29 within-team alignment and between-team behaviors that occur during the action phase of MTS performance. The taxonomy is built upon our model of MTS action subphases which delineates MTS action into three interrelated, multilevel phases: acting, monitoring, and recalibrating . We evaluate the content validity of the taxonomy using subject matter expert interviews and case studies within a US Navy context. We discuss implications regarding the applicability of the MTS action subphase framework and associated taxonomy for diagnostic and training purposes.